Phase characterization in crystallized glasses in the Na2O.2CaO.3SiO2- Na2O.3CaO.6SiO2 pseudo-binary system - Oliveira, Katherine Santos (2021)
Glass-ceramics are of the highest relevance in the industry due to their wide variety of uses. Compared to their parent glass, their enhanced properties result from the rigorous microstructure control during the precursor glass crystallization. Remarkably, the Na2O-CaO-SiO2 system is of great interest in the glass industry, finding applications from conventional windows, packaging, and tableware to bioglasses in medicine, among several others. The crystallization kinetics of stoichiometric compositions in this system has been extensively studied. However, there is a lack of information on the phases crystallized in the combeitedevitrite (Na2O·2CaO·3SiO2-Na2O·3CaO·6SiO2) pseudo-binary system. In this work, the phase formation in stoichiometric and non-stoichiometric compositions in the combeitedevitrite pseudo-binary join was investigated by X-ray diffraction (XRD), differential scanning calorimetry (DSC), optical microscopy and, scanning electron microscopy (SEM). In moderate undercooling below the liquidus, combeite was the primary phase crystallizing in all glasses of non-stoichiometric compositions treated close to the temperature of crystallization onset (about 750 °C) determined by DSC. In a glass of eutectic composition (33.3 mol% devitrite), the devitrite was observed only above 810 °C in advanced stages of crystallization. The devitrite formation was accompanied by a decrease in the volume fraction of the combeite solid solution. In contrast, in a hyper-eutectic composition (50 mol% devitrite), devitrite nucleated heterogeneously and grew from the surface of combeite crystals immediately after the combeite formation. The decomposition of devitrite into wollastonite and liquid occurred above 1050 °C for glasses with compositions between 33.33 and 93.75 mol% devitrite. Only glasses in the hypo-eutectic section of the combeite-devitrite binary system presented homogeneous nucleation. For these compositions, the combeite solid solution formation was investigated by XRD. It is suggested that combeite solid solution occurs in the interval between 0 and 33.33 mol% devitrite. The microstructure assessment in glass-ceramics from combeite-devitrite pseudo-binary glass compositions sheds light on the phase formation in this system, which is relevant for theoretical and practical applications.